Analisis Kinerja Keuangan Perusahaan Penerbangan pada Masa Pandemi Covid-19 - Ratna Kurniawati; Listyowati Listyowati (Jurnal Akuntansi dan Perpajakan, 2021)
This study aims to determine the impact of the COVID-19 pandemic on the financial performance of airlines as seen based on the ratio of liquidity, solvency, activity, and profitability. The subjects in this study were airlines listed on the IDX, which consisted of 3 companies, namely PT Garuda Indonesia (Persero) Tbk, PT Air Asia Indonesia Tbk, and PT Indonesia Transport Infrastructure Tbk. The data collection technique in this research is data documentation which comes from www.idx.co.id. The results of this study indicate that the COVID-19 pandemic has a negative impact on the financial performance of airlines. The decline in financial performance was marked by a decrease in the calculation results of the liquidity ratio, activity and profitability as well as an increase in the calculation results of the solvency ratio. Of the three airlines listed on the IDX, PT Air Asia Indonesia Tbk is the airline that experienced the greatest impact due to the COVID-19 pandemic, this is because prior to the COVID-19 pandemic, PT Air Asia Indonesia Tbk's business activities were mostly on outside travel. country, but at the time of the COVID-19 pandemic, many countries closed their access to foreign flights. While PT Indonesia Transport Infrastructure Tbk is an airline company whose financial performance has only experienced the least impact of the COVID-19 pandemic when compared to PT Air Asia Indonesia Tbk and PT Garuda Indonesia (Persero) Tbk because most of these business activities in this company are the transportation of goods such as oil and gas.